Contactless electrostatic detumbling of axi-symmetric GEO objects with nominal pushing or pulling. Issue 11 (1st December 2018) - Bennett, Trevor; Schaub, Hanspeter
Abstract: Large asset values of satellites and demand for orbital slots in the Geostationary orbit belt motivates on-orbit servicing and active debris removal strategies. The challenge of on-orbit capture of tumbling serviceable satellites or debris targets is primarily overcome by including a target detumble prior to any mechanical interface. Of the many methods proposed, touchless electrostatic detumbling shows significant advantages in collision avoidance and preservation of the target object. Previous studies demonstrated that the electrostatic interaction is sufficient to touchlessly despin the fixed-axis rotation of a rocket body-sized object within several days. This work focuses on large, generally tumbling axi-symmetric targets in the Geostationary Orbit which form a large component of the GEO debris population. The deep-space controller is augmented for tugging, pushing, and nominal detumbling configurations, providing a complete analysis of the stability and convergence properties. The effectiveness of this detumble control is numerically illustrated by simultaneously detumbling and tugging the target in GEO. The controller reduces the tumbling to the order of the mean motion allowing for mechanical docking methods.